Diagnóstico del virus Distemper y Parvovirus canino a través de kits rápidos y qPCR en la ciudad de Latacunga - Farías Román, María Laura (2021)
Distemper and canine Parvovirus, which are highly contagious diseases that affect any age dogs, although their incidence is higher in the less than one-year-old. The reliable diagnosis and opportune treatment improve the infected animals´ prognostic. So, it was compared the Distemper and canine Parvovirus diagnosis between the qPCR molecular test and the quick kits into domestic canines’ clinical cases, which come to veterinary centers in Latacunga city. It was analyzed 24 canine parvovirus samples, which 19 samples were positive to quick kits, they were found that 5 parvovirus samples diagnosed by quick kits with negative results were positive by real-time PCR, on the other hand 4 positive parvovirus samples per quick kits gave negative results to qPCR, this proves that it is a highly sensitive and highly specificity technique for virus detection, unlike quick kits. With canine Distemper there were problems by the standardization process, but from 6 positive Distemper samples diagnosed through quick kits, 2 gave positive qPCR results. The research results allow to set that qPCR is a recommended diagnostic technique for the Parvovirus and canine Distemper detection, since the results obtained by this technique are more reliable and faster. The quick tests used into the veterinary clinic that into this and other studies have shown their low sensitivity consistently